2006
DOI: 10.1128/jvi.80.8.4068-4078.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Regions of Virion-Associated Kaposi's Sarcoma-Associated Herpesvirus Complement Control Protein Required for Complement Regulation and Cell Binding

Abstract: Complement, which bridges innate and adaptive immune responses as well as humoral and cell-mediated immunity, is antiviral. Kaposi's sarcoma-associated herpesvirus (KSHV) encodes a lytic cycle protein called KSHV complement control protein (KCP) that inhibits activation of the complement cascade. It does so by regulating C3 convertases, accelerating their decay, and acting as a cofactor for factor I degradation of C4b and C3b, two components of the C3 and C5 convertases. These complement regulatory activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 60 publications
4
56
0
Order By: Relevance
“…A similar mechanism could also be operative for the interaction of VCP with C4b and factor I. Because domain requirements for ligand binding and CFAs in viral (34,48,49,54) and human complement regulators (55)(56)(57)(58)(59)(60)(61)(62) are conserved, it could be inferred that the recognition sites for C3b/C4b and factor I are spatially conserved in both human and viral complement regulators, and that they employ a common mechanism to inactivate C3b and C4b.…”
Section: Vcp Domains Critical For Factor I Cfasmentioning
confidence: 99%
“…A similar mechanism could also be operative for the interaction of VCP with C4b and factor I. Because domain requirements for ligand binding and CFAs in viral (34,48,49,54) and human complement regulators (55)(56)(57)(58)(59)(60)(61)(62) are conserved, it could be inferred that the recognition sites for C3b/C4b and factor I are spatially conserved in both human and viral complement regulators, and that they employ a common mechanism to inactivate C3b and C4b.…”
Section: Vcp Domains Critical For Factor I Cfasmentioning
confidence: 99%
“…Thus, KCP is likely to help protect virions and infected cells against complement eradication. Moreover, KCP may be multifunctional; we recently showed that, like other human and viral RCAs, it binds to heparin and heparan sulfate (27,40). On the surface of virions, KCP may therefore aid in viral attachment to host cells, as previously described for the envelope glycoproteins K8.1 and gB (1,3,9,44).…”
mentioning
confidence: 92%
“…Cells and debris were removed by centrifugation (1,900 ϫ g for 5 min at 4°C), and virions were then concentrated (13,000 ϫ g for 180 min at 4°C) before being resuspended in serum-free medium by overnight incubation at 4°C. The IEM procedure was performed essentially as described for staining KSHV virion-associated KCP (40). Briefly, RRV was applied to Parlodion-coated 200-mesh nickel grids (Agar Scientific, Stansted, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…expression vector (29). The pTorsten-A3Fc was produced by amplifying the A3 coding sequence by using the primers XbaI142S and A3deltastop (see Table 1 for the primer sequence) and the AlHV-1 BAC C500 as the template DNA.…”
mentioning
confidence: 99%